2005
DOI: 10.1093/jee/98.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Plant Growth Regulator Prohexadione-Calcium on Insect Pests of Apple and Pear

Abstract: The effect of prohexadione-calcium, a plant growth regulator that inhibits gibberellin metabolism, on Cacopsylla pyricoloa (Foerster) in pear trees, and Choristoneura rosaceana (Harris) and Aphis spireacola Patch, in apple trees was studied. C. pyricoloa and A. spireacola populations were significantly reduced in prohexadione-calcium-treated pear and apple, respectively. Insecticide control of both pests with imidacloprid was synergized in treatments with prohexadione-calcium. In apples treated with prohexadio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Several studies have demonstrated that the use of growth regulators reduced pear psylla populations and their damage (Lombard et al, 1982;Paulson et al, 2005). We found that oviposition rate, nymph survival and development rates, were lower in trees that had been treated with growth regulators.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Several studies have demonstrated that the use of growth regulators reduced pear psylla populations and their damage (Lombard et al, 1982;Paulson et al, 2005). We found that oviposition rate, nymph survival and development rates, were lower in trees that had been treated with growth regulators.…”
Section: Discussionsupporting
confidence: 52%
“…So far, it is not fully understood why these plant growth regulators inhibit psylla (Paulson et al, 2005). Our hypothesis was that growth regulators decrease the psylla population by reducing the nitrogen content of the growing shoots.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unfortunately, herbicide strips may also create problems, including soil erosion, reduced organic matter and leaching of nitrates into ground water (Sanchez et al 2003) plus increased incidence of plant diseases, insects and two-spotted spider mites, Tetranychus urticae Koch (Juvara-Bals et al 1990;Hardman et al 2005). Part of the reason for pest and disease problems is that the removal of competing ground cover vegetation promotes excessive growth of shoots which are prone to attack by pests and diseases (Brown and Glen 1999;Paulson et al 2005). Also leaf N is increased and levels of P and K are reduced (Johnson and Johnson 1980), changes which favour faster development and higher fecundity of T. urticae (Wermelinger et al 1991) and the European red mite Panonychus ulmi (Koch) ( Van de Vrie and Boersma 1970).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have demonstrated nontarget eVects of diVerent plant growth substances on insects (Posnova 1974;Schutte 1978;Kristiansen et al 1992;CoVelt et al 1993;Nazir Ahmad et al 2003). When combined with insecticides, plant growth substances cause additive or synergistic eVects on insects (Pasqualini et al 1997;Iob 2000;Paulson et al 2005). In some cases, they increase the resistance of the plants to insects (Zummo et al 1984;Attah and Emden 1993;Ahmad et al 2003).…”
Section: Introductionmentioning
confidence: 99%